Metabolic Profiling and Untargeted 1H-NMR-Based Metabolomics Study of Different Iranian Pomegranate (Punica granatum) Ecotypes - Hasanpour, Maede; Saberi, Satar; Iranshahi, Mehrdad (Planta Medica, 2020)
Pomegranate (Punica granatum) is an ancient fruit that is widely consumed as fresh fruit and juice. The aim of the present study was to compare the metabolic profile of pomegranate ecotypes from different geographical origins of Iran, the largest producer of pomegranates in the world. 1H-NMR and 2D NMR spectroscopy were applied to investigate the ecotypic variation. Multivariate data analyses were used to identify overall metabolic differences. Mazandaran pomegranate samples were found to be different from the other ecotypes, having a high content of citric and succinic acids. Bajestan, Ferdows, and Yazd pomegranates contained comparatively higher amounts of anthocyanins and ellagic acid derivatives than other pomegranate ecotypes. The distribution of metabolites among different ecotypes of pomegranate is discussed on the basis of these findings.
Keywords: anthocyanin; 1H-NMR-based metabolomics; metabolite profiling; Iranian pomegranate; Punica granatum; Lythraceae